PENGARUH GAYA KEPEMIMPINAN, PENGAWASAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN MAJENE - M. Ramli Sahur (Cross-border, 2021)
The objectives of the study were to: a) determine the effect of leadership style on employee performance at the Majene Regency Population and Civil Registry Office, b) determine the effect of supervision on employee performance at the Majene Regency Population and Civil Registry Office, c) determine the effect of work discipline on employee performance at The Office of Population and Civil Registry of Majene Regency and d) find out which variables have a more dominant influence on Employee Performance at the Office of Population and Civil Registry of Majene Regency. This study uses a quantitative approach. The research was conducted from March 2021 to June 2021 at the Majene Regency Population and Civil Registry Office. The sample consisted of 41 employees. The results showed that: 1) Leadership style had an effect on Employee Performance at the Department of Population and Civil Registry of Majene Regency, 2) Supervision had an effect on Employee Performance at the Department of Population and Civil Registry of Majene Regency, 3) Work Discipline had no effect on Employee Performance at the Department of Population and Civil Registry of Majene Regency and 4) Leadership Style Variable has more influence on Employee Performance at the Department of Population and Civil Registry of Majene Regency.